Developing Value Innovation Strategy In The "Blue Ocean Shift" Framework At The Flat Glass Industry In Indonesia - Rudy Subagio (IKAT: The Indonesian Journal of Southeast Asian Studies, 2020)
Competition in the flat glass market in Indonesia since 2015 has been increasingly severe because much imported glass has entered Indonesia. The rapid rate of imported glass is due to two factors:  the enactment of the free trade pact in Southeast Asia and the expansion of the Chinese glass factory that built new factories in the Southeast Asia region, especially in Malaysia. Most of the imported glass entering Indonesia is commodity glass at a lower than local products, so they have begun to take a portion of the market share of local products. This competition is getting more onerous because the local flat glass industry has difficulties in reducing the price to be equal or lower than competitors' price due to the production cost structure is already too high. This research explores the basic concepts of strategies carried out by local flat glass companies in the face of competition in the flat glass industry. This is based on the concept of value innovation in the framework of “blue ocean shift.”  The research method used is an exploratory case study draws on an in-depth field study conducted in a local flat glass company based in Indonesia.